Gender Issues and Women's Empowerment- A qualitative study in Jaffna district - Tharshiga, P.; Rathiranee, Y. (University of Jaffna, 2024)
Purpose: Women in Jaffna play a crucial role in the region's cultural, economic, and social fabric but face challenges shaped by traditional norms and post-conflict realities. These challenges include limited access to education, employment, and land ownership, with cultural factors often defining their roles. The present study wishes to examine the gender issues and women empowerment in Jaffna. The purpose of this research is to examine the gender-specific challenges women face in achieving financial independence, making decisions, and improving their social status. Design/Methodology/Approach: For the analysis, ten women in executive positions working in Jaffna were selected using a purposive sampling method. This study employed a qualitative approach, primarily relying on narratives. Thematic analysis was utilised to analyse and interpret the data collected from the interviews. Findings: The research findings revealed that gender issues are strongly influenced by cultural norms. Women tend to prioritise their families over their careers, reflecting societal expectations deeply rooted in tradition. This cultural framework creates significant challenges for women in balancing professional and personal responsibilities. Additionally, the study highlighted that many women prefer to depend on men for decision-making, further emphasizing the influence of traditional gender roles. Research limitations: Limitations of the research are topic is very sensitive. Additionally, women in the Jaffna district may not have had a comprehensive understanding of gender issues, which likely affected the depth and clarity of their responses. Implications: The study implies that efforts to empower women through economic initiatives may face limited success unless the deeply ingrained cultural barriers are addressed.
Keywords: Gender issues; Financial independence; Decision making; Social status improvement